The relationship between financial development level and economic growth : Azerbaijan case - Abdullayeva, Saadat (2022)
If the financial system is well-functioning and financial development is established, economic growth will follow. The goal of this study is to assess Azerbaijan's financial policies and examine the country's financial structure in light of financial development indicators. Simultaneously, another goal is to uncover the link between credit and M3 money supply, which have been chosen as indices of financial growth, and GDP. The research question of the thesis is the following: What is the relationship between financial development level and GDP?, What are the policies implemented by Central Bank of Azerbaijan in order to ensure financial stability? The study is organized into three parts, the first of which delves deeply into the concepts of financial development and economic growth. The first portion explains the ideas of financial development and financial system, followed by explanations of the financial system's operations, financial development measurement, economic growth, and economic growth theories in the second and third sections. The financial system of Azerbaijan was then examined in the research's second component. Finally, an empirical analysis was undertaken after a review of the relevant literature and the influence of financial development on the Gross Domestic Product (GDP) between 2005 and 2019.